The Constructivist Principle of Learning by Being in Physics Teaching - Mihail Calalb (Athens Institute for Education and Research, 2023)
A detailed characteristic of teaching and learning approaches used within the new concept of Learning by Being (LBB) is given. The evolution of educational paradigms from Learning by Doing (LBD) and Learning by Understanding (LBU) toward LBB is analyzed. The basic idea of LBB is students' ownership on cognitive goals, or the assumption of learning objectives, in other words - intrinsic motivation of students. Along with LBB, the author proposes the term of guided self-scaffolding. Both terms tend to accentuate high level of student's intrinsic motivation. The article examines the school physics lab as an example of constructivist learning environment and analyzes several didactic approaches as inquiry-based learning, problem-based learning, project-based learning, case studies, and just in time teaching from constructivist point of view. The author enumerates the basic principles for the organization of school physics lab in a constructivist manner: provision of opportunities for students' own thinking, giving students a certain freedom degree in identifying solution through verbalization of the problem, necessity for teacher to know a priori concepts of students, students' effort as a mandatory condition to achieve students' interest. The concept of "big scientific ideas" is in the core of this organization. The author emphasizes that conceptual understanding in school physics lab, which is inseparable from learning by being, is achieved through the overlapping of several learning and teaching approaches which form the core of LBB concept.